POSITIVE RESULTS OF TRANSPLANTATION OF MULTI-COMPONENT COMPOSITE MATERIAL CONTAINING ALLOGENEIC MESENCHYMAL STEM CELLS AFTER CYSTECTOMY IN A RABBIT - N. V. Orlovа; T. I. Vinogrаdovа; N. M. Yudintsevа; Yu. A. Nаsсhekinа; M. G. Sheykhov; P. K. Yablonsky (Туберкулез и болезни лёгких)
Of late much attention has been paid to tissue engineering by urologists. After successful testing on animals, artificial urinary bladders with self-specific cells were transplanted to humans. Our research is aimed at investigating the opportunity of using cellular technologies  if no healthy  self-specific material is available.The goal of this experiment  is to investigate the opportunity of using a multi-component composite material containing  allogeneic cells to replace the defect of urinary wall under experimental conditions.The standard technique was used for isolation and culturing of mesenchymal stromal stem cells from the rabbit's  bone marrow. Multi-component composite material based on the polylactide  matrix was inoculated by allogeneic cells and transplanted in vivo to the model of partial cystectomy. In 2.5 months the presence of labeled cells in the implantation site was confirmed by objective methods.